2003
DOI: 10.1177/135481660300900303
|View full text |Cite
|
Sign up to set email alerts
|

Innovation in the Tourism Sector: Results from a Pilot Study in the Balearic Islands

Abstract: This paper provides empirical evidence on innovation in various tourism firms in the Balearic Islands. The main results from this pilot study are as follows. Innovation is common in Balearic tourism firms, especially in the lodging and accommodation sector. Process, delivery and organizational changes are the most frequent forms of innovation. Non-technological innovation is common, especially in the lodging and accommodation sector. Technological innovation relates mainly to information and communication tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0
10

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 6 publications
3
62
0
10
Order By: Relevance
“…Another reason is the more and more intense competition in tourism. In such market conditions, there is a general consensus that competitiveness of tourism enterprises increasingly depends upon their innovation activity bringing about lower costs and/or higher quality output Gnoth, 2005, Chadee andMattsson, 1996;Mattsson and Or…la-Sintes, 2009 (Hjalager, 1997, 2002, Jacob et al , 2003Nordin, 2003;OECD, 2003;Sørensen, 2004;Volo, 2004Volo, , 2005Frechse, 2005, Pikkemaat andPeters, 2005;Pechlaner et al, 2005;Weiermair, 2005;Mattsson et al, 2005, Or…la-Sintes et al, 2005Walder et al (Eds. ), 2006;Or…la-Sintes and Mattsson, 2007, Ottenbacher and Gnoth, 2005, Novelli et al 2006Sundbo et al 2007;Pikkematt and Weiermar, 2007;Hall and Williams, 2008;Hjalager et al, 2008;Pikkemaat, 2008;Hall, 2009, Mattsson andHjalager, 2010 Hjalager (2010, p. 1) that "innovation has become a buzzword which in many cases is used without deeper re ‡ection for anything that is moderately novel" points out to a needed caution and academic rigour in discussion and research on this complex and important issue.…”
Section: Innovation In Tourism -Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Another reason is the more and more intense competition in tourism. In such market conditions, there is a general consensus that competitiveness of tourism enterprises increasingly depends upon their innovation activity bringing about lower costs and/or higher quality output Gnoth, 2005, Chadee andMattsson, 1996;Mattsson and Or…la-Sintes, 2009 (Hjalager, 1997, 2002, Jacob et al , 2003Nordin, 2003;OECD, 2003;Sørensen, 2004;Volo, 2004Volo, , 2005Frechse, 2005, Pikkemaat andPeters, 2005;Pechlaner et al, 2005;Weiermair, 2005;Mattsson et al, 2005, Or…la-Sintes et al, 2005Walder et al (Eds. ), 2006;Or…la-Sintes and Mattsson, 2007, Ottenbacher and Gnoth, 2005, Novelli et al 2006Sundbo et al 2007;Pikkematt and Weiermar, 2007;Hall and Williams, 2008;Hjalager et al, 2008;Pikkemaat, 2008;Hall, 2009, Mattsson andHjalager, 2010 Hjalager (2010, p. 1) that "innovation has become a buzzword which in many cases is used without deeper re ‡ection for anything that is moderately novel" points out to a needed caution and academic rigour in discussion and research on this complex and important issue.…”
Section: Innovation In Tourism -Literature Reviewmentioning
confidence: 99%
“…Therefore, Hall and Williams (2008) and Hall (2009) conclude that there is an obvious need for better empirical evidence on innovation in tourism and that its quanti…cation is an essential need. One of the ways is to include the tourism "industry" in an adequate way in the existing research, such as CIS (Jacob et al, 2003). Alternatively, the development of tourism speci…c methodologies is an option.…”
Section: Innovation In Tourism -Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Drawing upon the work of Jacob et al (2003) and Orfila-Sintes et al (2005), three dimensions of innovation in hotels are identified: products, processes and market/organisational (Sundbo & Galloouj, 1998). The first dimension relates to product enhancement and differentiation, which aim to improve customer experiences by creating new combinations or sets of services (Norman, 1984), including more environmentally sustainable products (Williams & Shaw, 1998).…”
Section: Migration Experience and Innovation Performancementioning
confidence: 99%
“…Hoffman et al (1998) specifically argue that such a relationship generally exists for small and medium sized firms. However, there is almost no systematic research on this issue in respect of hotels, with the exception of Jacob et al's (2003) work on the Balearic Islands, which found positive but often complex relations between innovation and different aspects of firm performance. These complexities are important because it can not simply be assumed that innovation automatically contributes to firm performance in a positive way.…”
Section: An Overview Of Innovations and Their Impact On The Businessmentioning
confidence: 99%